Resistance that Cannot Be Recognized as Such: Interview with Gayatri Chakravorty Spivak: Rezistenca e cila nuk mund të njihet si e tillë: Intervistë me Gayatri Chakravorty Spivak - Milevska, Suzana; Spivak, Gayatri Chakravorty; Hodja, Mirushe (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Suzana Milevska and Gayatri Chakravorty Spivak | Сузана Милевска и Гајатри Чакраворти Спивак Title (English): Resistance that Cannot Be Recognized as Such: Interview with Gayatri Chakravorty Spivak Title (Albanian): Rezistenca e cila nuk mund të njihet si e tillë: Intervistë me Gayatri Chakravorty Spivak Translated by (English to Albanian): Mirushe Hodja Transcribed by: Robert Alagjozovski Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 27-45 Page Count: 18 Citation (English): Suzana Milevska and Gayatri Chakravorty Spivak, “Resistance that Cannot be Recognized as Such: Interview with Gayatri Chakravorty Spivak,” Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003): 27-45. Citation (Albanian): Suzana Milevska dhe Gayatri Chakravorty Spivak, „Rezistenca e cila nuk mund të njihet si e tillë: Intervistë me Gayatri Chakravorty Spivak“, përkthim nga Anglishtja Mirushe Hodja, Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003): 27-45.